Towards a Psychology of Global Consciousness Through an Ethical Conception of Self in Society. (24th January 2016) - Liu, James H.; Macdonald, Matthew
Abstract: Globalization has brought people around the world closer together in ways that have created greater uncertainty in their identity politics. This has sometimes strengthened local identities, despite attempts to create 'universal' forms of identity that impose one standard of appropriate conduct in the face of difference. Drawing from Dialogical Self Theory and from cosmopolitanism, we propose that adequately responding to the ethical and identity challenges presented by globalization requires having Global Consciousness: "a knowledge of both the interconnectedness and difference of humankind, and a will to take moral actions in a reflexive manner on its behalf". We argue that this approach can ground a distinctively normative psychology of globalization. We consider negative and positive aspects of the golden rule in equal and close relationships, and benevolence in unequal power relationships as behaviour guides for global consciousness, and theorize about institutional leadership that supports the provision of public goods. We offer empirical tests of this approach.